WIFE CONTRIBUTION TO FISHERMAN HOUSEHOLD INCOME IN MERANTI BUNTING VILLAGE MERBAU DISTRICT MERANTI ISLAND REGENCY RIAU PROVINCE - Cahyati, Eka Nur; Bathara, Lamun; ', Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in January 2016 in the Meranti Bunting Village Merbau District Meranti Island Regency Riau Province. The objective of the study are to indentify the types of activities of the fisherman’s wife, to know the reasons fisherman’s wife worked, the utilization time fisherman’s wife and the fisherman’s wife contributes increasing in fisherman household incomes. The method use in this research is survey method with census sampling as many as 30 wife of fishermen. The results showed that the fisherman’s wife did domestic work such as cooking, washing, caring for children an others, and public works is as fish seller, the areca seller, processing of fisheries product and daily traders. Reasons fisherman’s wife worked most favor are economic pressures. Fisherman’s wife at most their time to domestic work which is an average of 43 hours/week or 6 hours/day. Their contributon given by the wife of a fisherman belonging to a low level, namely 26,9% although the contribution made low but it helps the household economy Meranti Bunting Village.Keywords : Fisherman’s wife, fishermen household income, contributions